Is the Swedish FRAX model appropriate for Swedish immigrants?. Issue 11 (November 2015) - Johansson, H.; Odén, A.; Lorentzon, M.; McCloskey, E.; Kanis, J.; Harvey, N.; Karlsson, M.; Mellström, D.
Abstract Summary The incidence of hip fracture in Sweden is substantially lower in immigrants than in the population born in Sweden. Thus, the use of a FRAX® model in immigrants overestimates the risk of fracture, and the use of country of origin-specific models may be more appropriate. Introduction Age-specific fracture and mortality rates vary between countries so that FRAX tools are country-specific. In the case of immigrants, it is not known whether the model for the original or the new country is most appropriate. The aim of this study was to compare the incidence of hip fractures in foreign-born and Swedish-born individuals residing in Sweden. Methods We studied the incidence of hip fracture in all men and women aged 50 years or more in Sweden between 1987 and 2002. The population comprised 2.8 million Swedish-born and 270, 000 foreign-born individuals. Results Incident hip fractures occurred in 239, 842 Swedish-born and 12, 563 foreign-born individuals. The hip fracture incidence rose with age for both groups and was higher for women than men amongst both Swedish-born and foreign-born individuals. The hip fracture incidence for the Swedish-born cohort was approximately twice that of immigrants. For example, at the age of 70 years, the annual hip fracture incidence (per 100, 000) was 450 (95 % CI 446–454) for a Swedish-born woman and 239 (95 % CI 223–257) for a foreign-born woman at the time of immigration. The hip fracture incidence rose slowly with time from immigration (0.6 % per annum, 95 % CI 0.5–0.8 %) but remained significantly lower than for Swedish-born individuals even after 40 years of residence. Conclusions The incidence of hip fracture in Sweden is substantially lower in immigrants than in the population native to Sweden. Although there was a small rise in age- and sex-specific incidence after immigration, the incidence remained markedly lower than that observed in Swedish-born individuals. Thus, the use of a FRAX model for Sweden will overestimate the risk of fracture for foreign-born individuals living in Sweden.